Analisis Transformasi Kebijakan Pendidik Tingkat PAUD hingga Sekolah Menengah: Tinjauan MSDM Strategis dalam Implementasi Standar Kemendikdasmen - Radiana Rosada; Rochmatunnisa Rochmatunnisa; Nuryadin Nuryadin (MAN 4 Kota Pekanbaru, 2026)
Educator standard policies in Indonesia often remain formal administrative milestones, sidelining actual teaching quality. This study analyzes the effectiveness of teacher standard policies across all education levels in Indonesia, from qualification and certification regulations to recent pedagogical and digital reforms, through a strategic human resource management (HRM) lens. Using a literature review, the study analyzed 13 peer-reviewed articles (2021–2025), selected for relevance, credibility, and recency, applying William Dunn's (2003) policy analysis model for its critical, prescriptive approach. Findings reveal a systemic paradox: despite 97.33% compliance with S1/D4 qualifications, average teacher competency scores (UKG) remain only 50.64/100, suggesting certification functions as an administrative formality rather than a driver of substantive competency. This pattern is compounded by limited PPPK recruitment (23–33% of target) and Indonesia's low 2023 TIMSS ranking (68th of 80 countries). The study concludes that curricular and technological innovations risk failing without a shift toward humanistic, strategic HRM.